2019
DOI: 10.1186/s42787-019-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal heat generation on free convective power-law variable temperature past a vertical plate considering exponential variable viscosity and thermal conductivity

Abstract: The aim of this paper is to study the free convection boundary-layer flow with heat generation and variable fluid properties past a vertical plate. We incorporated the heat generation and variable viscosity are the exponential decay form and thermal conductivity is the linear form in the governing equation. Using similarity transformations, the governing coupled non-linear partial differential equations are transformed into a system of coupled non-linear ordinary differential equations and then solved using Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Shamshuddin et al [8] examined the contribution of variable viscosity while reporting the heat transfer aspects in nanofluid flow via rotating disk. Ferdows et al [9] explained the assessment of internal heat transfer applications for power law fluid with attribution of exponential fluid viscosity. The heat transfer analysis in the MOS2 and Fe3O4 nanoparticles with ethylene glycol base liquid have been treated by Shamshuddin et al [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shamshuddin et al [8] examined the contribution of variable viscosity while reporting the heat transfer aspects in nanofluid flow via rotating disk. Ferdows et al [9] explained the assessment of internal heat transfer applications for power law fluid with attribution of exponential fluid viscosity. The heat transfer analysis in the MOS2 and Fe3O4 nanoparticles with ethylene glycol base liquid have been treated by Shamshuddin et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ferdows et al [9] explained the assessment of internal heat transfer applications for power law fluid with attribution of exponential fluid viscosity. The heat transfer analysis in the MOS2 and Fe3O4 nanoparticles with ethylene glycol base liquid have been treated by Shamshuddin et al [9]. Farajollahi et al [10] suggested the heat transfer mechanism in conical turbulators by utilizing the tiny particles.…”
Section: Introductionmentioning
confidence: 99%
“…Rashidi et al, [13] and Dhanai et al, [14] studied combined free and forced or mixed convective nanofluid flow over inclined surfaces and very recently Rihan [15] and Mkhatshwa et al, [16] studied mixed convection flow over vertical cylinder. Convection with power law wall temperature distribution were studied by Ali [17] and Ferdows et al, [18] where Ferdows et al, [18] investigated wall temperature variations for natural convection along vertical plate and Muñoz-Cobo et al, [19], Kim et al, [20] investigated for cylindrical surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…They observed a decline in the magnitude of velocity field as well as pressure inside the boundary layer with increasing values of the magnetic parameter. The free-convection boundary-layer flow with heat generation and variable fluid properties past a vertical plate with exponential variable viscosity and thermal conductivity have been investigated by Ferdows et al (2019). Yang and Lin (2019) studied the flow and heat transfer of non-Newtonian power-law fluid over a stretching sheet in the presence of the variable thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%